Effect of ginger essential oil and 6-gingerol on a multispecies biofilm of Listeria monocytogenes, Salmonella Typhimurium, and Pseudomonas aeruginosa - dos Santos, Emanoelli Aparecida Rodrigues [UNESP]; Tadielo, Leonardo Ereno [UNESP]; Schmiedt, Jhennifer Arruda; Possebon, Fábio Sossai [UNESP]; Pereira, Maria Olivia; Pereira, Juliano Gonçalves [UNESP]; dos Santos Bersot, Luciano (Springer Nature, 2023)
The objective of this study was to evaluate the potential antimicrobial and antibiofilm effect of ginger essential oil (GEO) and 6-gingerol on a multispecies biofilm formed by Listeria monocytogenes, Salmonella Typhimurium, and Pseudomonas aeruginosa on a polypropylene surface. The minimum inhibitory concentration concentrations obtained for GEO were 100 and 50 mg/mL and for 6-gingerol 1.25 mg/mL. Sessile cell counts ranged within 5.35–7.35 log CFU/cm2 in the control biofilm, with the highest sessile growth at 72 h. GEO treatments acted on the total population regardless of concentration at 1 and 48 h. L. monocytogenes behaved similarly to the total population, showing GEO action at 1 h and keeping the same pattern at 48, 72, and 96 h. Better action on S. Typhimurium was obtained at times of 1, 72, and 96 h. P. aeruginosa showed logarithmic reduction only when treated with GEO 50 mg at 24 h. As for 6-gingerol, in general, there was no significant action (p > 0.05) on the evaluated sessile cells. GEO showed antimicrobial activity against L. monocytogenes, S. Typhimurium, and P. aeruginosa, acting as an inhibitor of biofilm formation. As for 6-gingerol, it was considered a possible antimicrobial agent but without efficacy during biofilm formation.
Keywords: Antibacterial; Antibiofilm; Control methods; Essential oils